Penurunan berat badan setelah 12 minggu latihan beban menggunakan resistance band pada mahasiswa yang mengalami obesitas - Kuswahyudi, Kuswahyudi; Taufik, Muhamad Syamsul; Setiakarnawijaya, Yasep; Hazar, Fatih; Purwoto, Septyaningrum Putri (Universitas Nusantara PGRI Kediri, 2024)
Obesity among college students poses a significant health concern, as excess weight heightens the risk of various diseases. The study aims to determine the effects of a 12-week resistance band weight training program on weight loss in obese college students. This research employs an experimental method, specifically using a